Pojam termina integralni, multimodalni i kombinirani transport - Svetopetrić, Ivan (Promet - Traffic&Transportation, 2012)
There exists no uniform definition of the terms of integrated, multi-modal and combined transport. The paper provides a review and a sort of delineation of the terms of integrated, multi-modal and combined transport.